Comparison of Serum Hemagglutinin and Neuraminidase Inhibition Antibodies After 2010–2011 Trivalent Inactivated Influenza Vaccination in Healthcare Personnel. (3rd January 2015) - Laguio-Vila, Maryrose R.; Thompson, Mark G.; Reynolds, Sue; Spencer, Sarah M.; Gaglani, Manjusha; Naleway, Allison; Ball, Sarah; Bozeman, Sam; Baker, Steven; Martínez-Sobrido, Luis; Levine, Min; Katz, Jackie; et al.
Abstract: Background.  Most inactivated influenza vaccines contain purified and standardized hemagglutinin (HA) and residual neuraminidase (NA) antigens. Vaccine-associated HA antibody responses (hemagglutination inhibition [HAI]) are well described, but less is known about the immune response to the NA. Methods.  Serum of 1349 healthcare personnel (HCP) electing or declining the 2010–2011 trivalent-inactivated influenza vaccine ([IIV3], containing A/California/7/2009 p(H1N1), A/Perth/16/2009 [H3N2], B/Brisbane/60/2008 strains) were tested for NA-inhibiting (NAI) antibody by a modified lectin-based assay using pseudotyped N1 and N2 influenza A viruses with an irrelevant (H5) HA. Neuraminidase-inhibiting and HAI antibody titers were evaluated approximately 30 days after vaccination and end-of-season for those with polymerase chain reaction (PCR)-confirmed influenza infection. Results.  In 916 HCP (68%) receiving IIV3, a 2-fold increase in N1 and N2 NAI antibody occurred in 63.7% and 47.3%, respectively. Smaller responses occurred in HCP age >50 years and those without prior 2009–2010 IIV3 nor monovalent A(H1N1)pdm09 influenza vaccinations. Forty-four PCR-confirmed influenza infections were observed, primarily affecting those with lower pre-exposure HAI and NAI antibodies. Higher pre-NAI titers correlated with shorter duration of illness for A(H1N1)pdm09 virus infections. Conclusions.  Trivalent-inactivated influenza vaccine is modestly immunogenic for N1 and N2 antigens in HCP. Vaccines eliciting robust NA immune responses may improve efficacy and reduce influenza-associated morbidity.